2015
DOI: 10.1007/s10461-015-1100-4
|View full text |Cite
|
Sign up to set email alerts
|

Internalized HIV and Drug Stigmas: Interacting Forces Threatening Health Status and Health Service Utilization Among People with HIV Who Inject Drugs in St. Petersburg, Russia

Abstract: Marked overlap between the HIV and injection drug use epidemics in St. Petersburg, Russia, puts many people in need of health services at risk for stigmatization based on both characteristics simultaneously. The current study examined the independent and interactive effects of internalized HIV and drug stigmas on health status and health service utilization among 383 people with HIV who inject drugs in St. Petersburg. Participants self-reported internalized HIV stigma, internalized drug stigma, health status (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 59 publications
3
50
0
1
Order By: Relevance
“…These variables are consistent with and supported by the existing literature, which have identified the role of demographics (e.g. gender), a new HIV diagnosis, depressive symptoms and social support as impacting the relationship between stigmatizing experiences and substance use (18, 21, 22, 50-53). …”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…These variables are consistent with and supported by the existing literature, which have identified the role of demographics (e.g. gender), a new HIV diagnosis, depressive symptoms and social support as impacting the relationship between stigmatizing experiences and substance use (18, 21, 22, 50-53). …”
Section: Methodssupporting
confidence: 88%
“…While qualitative studies reveal that HIV may serve as a trigger for substance use and different stigmatized identities may lead to intensified experiences of stigma (i.e. “double stigma,” “multiple stigmas”, “interacting stigmas”) (11, 21, 22), a recent systematic review of the impact of HIV stigma on a range of health outcomes did not identify any studies focused on substance use (12). Furthermore, to inform the development of future interventions that may promote resilience to HIV stigma and buffer its harmful effects (23), it is important to understand the role of potentially modifiable factors; social support is one such factor (24).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicated that participants perceived internalized stigma as deterring some methadone clients from initiating ART. Research conducted in Russia with people who inject drugs similarly demonstrated that internalized and anticipated HIV and drug stigmas were correlated with lower rates of health service utilization and poor health (Burke et al, 2015; Calabrese et al, 2015). Some participants also reported that stigma at HIV clinics due to their history of drug addiction dissuaded some methadone clients from attending their medical visits at the HIV clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Despite people who use drugs (PWUD) contributing less to HIV incidence in the U.S. recently (Centers for Disease Control and Prevention, 2014), they remain a priority population for HIV prevention because of potential HIV transmission associated with preventable drug-related (e.g., needle-sharing) and sex-related (e.g., condomless sex) risk behaviors (Alipour et al, 2013; Marshall et al, 2014; Nadol et al, 2016; Volkow and Montaner, 2011). PWUD are affected by multi-level barriers to treatment and prevention such as stigma, discrimination, and social marginalization, thus posing a formidable challenge to access HIV services (Calabrese et al, 2016; Van Boekel et al, 2013). Failing to effectively intervene with PWUD has resulted in poor individual outcomes and threatens public health by increasing the likelihood continued HIV transmission by PWUD who remain undiagnosed or off treatment with persistent HIV viremia.…”
Section: Introductionmentioning
confidence: 99%